Assessment of wetland loss through industrialization and community expansion: a case study of the greater amanzule wetland in the Ellembelle district of Ghana - Dawuda, Usman Kaku; Yonghong, Cao; Al-Masnay, Yousef Ahmed; Al-Aizari, Ali Rajeh; Alzahrani, Hassan; Nizeyimana, Jean Claude; Zhang, Yue; Tong, Haoyu (Frontiers in Environmental Science, 2024)
Wetland ecosystems provide numerous services to humanity and the biosphere at large. However, these services are constantly dwindling due to the massive wetland loss caused by urbanization. Urbanization-induced wetland loss is a global problem, with most developing countries experiencing it currently. Several studies on wetland loss have been conducted. However, there is a dearth of studies integrating GIS and other ecological models to estimate the periodic deterioration of wetlands in rural settings in underdeveloped nations. As a result, this study aims to determine wetland loss in a developing country's countryside, using the Greater Amanzule Wetland in the Ellembelle District of Ghana as a case study. The study used the GIS and Remote Sensing dataset, the Normalization Difference Vegetation Index, and the InVEST-Habitat Quality model to analyze the spatial pattern of wetland loss and habitat quality variations caused by industrialization and community expansions between 2000 and 2020. Our results indicate that, from 2000 to 2015, community built-up and industrial land areas grew from 25.19ha to 84.21ha and 0 to 4.71ha respectively, causing a wetland loss of -39.64ha (-31.10%). Between 2015 and 2020, community built-up land grew to 78.65ha while industrial land slightly reduced to 2.54ha, leading to the wetland degradation of approximately -69.06ha (-42.53%). Wetland habitat quality steadily declined, from 0.97 in 2000 to 0.93 in 2015 and 0.93 in 2020. The study findings led to policy recommendations to reduce wetland encroachment and enhance sustainability.These recommendations included conducting effective land-use plan inspections before issuing permits, coordinating effective management, and promoting the recovery of natural and artificial vegetation to sustain the wetland.